2014
DOI: 10.3390/toxins6102932
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Limitation Promotes Accumulation and Suppresses Release of Cylindrospermopsins in Cells of Aphanizomenon Sp.

Abstract: As the biosynthesis of cylindrospermopsin (CYN) is assumed to depend on nitrogen availability, this study investigated the impact of nitrogen availability on intra- and extracellular CYN and deoxy-CYN (D-CYN) contents in three Aphanizomenon strains from temperate waters. Nitrogen deficient (−N) cultures showed a prolonged growth phase and intracellular toxin accumulation by a factor of 2–6. In contrast, cultures with additional nitrate supply (+N) did not accumulate CYN within the cells. Instead, the maximum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…However, in other freshwater cyanobacterial species capable of CYN production, Q CYN has been shown to differ over the growth cycle and under different light in Oscillatoria (Bormans et al, 2013). It also varies in response to P and N in Aphanizomenon ( Bar-Yosef et al, 2010;Preußel et al, 2009Preußel et al, , 2014, suggesting that CYN may have a different role in these species, or be under different metabolic controls. Ecotype CS-506 had a 6-fold higher Q CYN than CS-505.…”
Section: Discussionmentioning
confidence: 99%
“…However, in other freshwater cyanobacterial species capable of CYN production, Q CYN has been shown to differ over the growth cycle and under different light in Oscillatoria (Bormans et al, 2013). It also varies in response to P and N in Aphanizomenon ( Bar-Yosef et al, 2010;Preußel et al, 2009Preußel et al, , 2014, suggesting that CYN may have a different role in these species, or be under different metabolic controls. Ecotype CS-506 had a 6-fold higher Q CYN than CS-505.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested, the lowest CYN levels found in sediments representing the mid-Holocene period correlated with low N/P values, which may be an indication that limited N availability in the lake triggered CYN production [33]. However, experimental data suggests that under N limitation, the release of the toxin is highly suppressed, while additional nitrate supply highly promotes this process [90]. On the other hand, N depletion was demonstrated to cause an increase in intracellular pool [90]-it cannot be ruled out that N-starved cyanobacteria cells deposited in sediments contributed to sedimentary pool of CYN.…”
Section: Cylindrospermopsin (Cyn)mentioning
confidence: 91%
“…On the other hand, N depletion was demonstrated to cause an increase in intracellular pool [90]-it cannot be ruled out that N-starved cyanobacteria cells deposited in sediments contributed to sedimentary pool of CYN. In contrast, there is experimental evidence that P starvation may induce CYN synthesis and release [76,90,91]. No apparent association of that kind between sedimentary P and CYN levels were found in Lake Griffin.…”
Section: Cylindrospermopsin (Cyn)mentioning
confidence: 95%
See 1 more Smart Citation
“…Aside from its toxicity aspects, CYN is also interesting from a purely ecological point of view. Several studies have addressed questions regarding conditions that can trigger CYN production/secretion and demonstrated that it is more anticipated under nutrient deficiency (Preußel et al 2014). Could it therefore mediate an adaptive response in an unfavorable environment and physiological stress?…”
mentioning
confidence: 99%